2012
DOI: 10.1109/twc.2012.061912.111751
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Multicell Beamforming Design Approaching Pareto Boundary with Max-Min Fairness

Abstract: This paper addresses coordinated downlink beamforming optimization in multicell time-division duplex (TDD) systems where a small number of parameters are exchanged between cells but with no data sharing. With the goal to reach the point on the Pareto boundary with max-min rate fairness, we first develop a two-step centralized optimization algorithm to design the joint beamforming vectors. This algorithm can achieve a further sum-rate improvement over the max-min optimal performance, and is shown to guarantee m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 31 publications
0
72
0
Order By: Relevance
“…And the detail of the first 20 alternative iterations is shown in Figure 6b. We can see that the Loop1 represented by blue block has successfully maximize problem (8), and the Loop2 indicated by purple block has accomplished the minimization procedure of (13). Through alternatively manipulating the two loops, the lower bound of network capacity can converge to a saddle point which is equal to the optimal point of (4).…”
Section: Parameters Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…And the detail of the first 20 alternative iterations is shown in Figure 6b. We can see that the Loop1 represented by blue block has successfully maximize problem (8), and the Loop2 indicated by purple block has accomplished the minimization procedure of (13). Through alternatively manipulating the two loops, the lower bound of network capacity can converge to a saddle point which is equal to the optimal point of (4).…”
Section: Parameters Valuesmentioning
confidence: 99%
“…Furthermore, it can be observed that x ∈ C K×Q is a global variable coupling among different objective functions and the constraint C 3 in (8). The Lagrangian function of (8) can be expressed as:…”
Section: Loop1 Design: Uplink Power and Beamforming Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For weighted max-min optimization with a total power constraint, there are computation-ally efficient fixed-point algorithms [42,208,226,228,296] that are also amenable to distributed implementation [42,59,208]. These algorithms are less suitable under general multi-cell power constraints, although such constraints can be handled exactly for single-antenna transmitters [43], by iterative subgradient methods for multi-antenna transmitters [59,308], or by suboptimal approximation of the power constraints [43,108]. Furthermore, the beamforming parametrization with interference-temperature constraints in Theorem 3.2 enables a simple decentralized algorithm for moving an operating point toward the Pareto boundary [325].…”
Section: Algorithm 4: Distributed Optimization With Qos Requirementsmentioning
confidence: 99%
“…Coordinated or cooperative beamforming, where multiantenna reprocessing at neighboring base stations (BSs) are designed cooperatively, has been extensively studied in the existing literatures such as [3][4][5][6][7][8][9] and thereof. To be more specific, the transmit power minimization problem subject to signal-to-interference-and-noise-ratio (SINR) constraints at the remote users was addressed based on *Correspondence: huangym@seu.edu.cn 1 School of Information Science and Engineering, Southeast University, Nanjing 210096, China Full list of author information is available at the end of the article the uplink-downlink duality theorem for multicell multiuser downlink systems [3].…”
Section: Introductionmentioning
confidence: 99%